THE IMPLEMENTATION OF INSTRUCTIONAL MODEL LEARNING CYCLE (LC) â€œ5Eâ€ ASSISTED WITH INTERACTIVE LKS WITH BLOG-BASED TO IMPROVE LEARNING RESULT ON TECHNOLOGY INFORMATION AND COMMUNICATION SUBJECT IN IPA 3 CLASS SMAN 2 SINGARAJA AT ACADEMIC YEAR 2012/2013 - Artha Kusuma, Febriana (Universitas Pendidikan Ganesha, 2013)
This research is aimed to (1) improve the result of learning Technology Information and Communication for students on science class (IPA) grade XI in SMAN 2 Singaraja through the implementation of instructional model learning cycle 5E assisted with interactive LKS with Blog-based, and (2) to know the studentsâ€™ response in science class grade XI toward the implementation of instructional model learning cycle 5E assisted with interactive LKS with Blog-based on Technology Information and Communication subject.This Research is classroom action research with two cycles. Each cycle consists of 4 steps. The first step is the planning of action, the second step is action, the third step is observation and Evaluate, and the fourth step is reflection. Subjects in this research are students in science class XI IPA 3 SMAN 2 Singaraja in academic year 2012/2013 that consist of 31 students. The objects of this research are (1) studentsâ€™ result, and (2) studentsâ€™ responses toward the implementation of instructional model learning cycle 5EÂ on Technology Information and Communication subject. The data is obtained through test and observation, and the data for studentsâ€™ response is obtained through questionnaire. The data obtained is analyzed descriptively.Â Â Based on the results of analysis data obtained, the results show that there is improvement or progress on students result in learning TIK. On the first cycle, the average of students scores are 77,88 and the percentage of students success are 70,96%. On the second cycle, there is significant improvement become 84,62 and 83,87%. Studentsâ€™ response in implementing learning cycle 5E in learning TIK can be categorized in positive category with the average scores 47.Â